An immunogold single extracellular vesicular RNA and protein (AuSERP) biochip to predict responses to immunotherapy in non‐small cell lung cancer patients. Issue 9 (12th September 2022) - Nguyen, Luong T. H.; Zhang, Jingjing; Rima, Xilal Y.; Wang, Xinyu; Kwak, Kwang Joo; Okimoto, Tamio; Amann, Joseph; Yoon, Min Jin; Shukuya, Takehito; Chiang, Chi‐Ling; Walters, Nicole; Ma, Yifan; et al.
Abstract: Conventional PD‐L1 immunohistochemical tissue biopsies only predict 20%–40% of non‐small cell lung cancer (NSCLC) patients that will respond positively to anti‐PD‐1/PD‐L1 immunotherapy. Herein, we present an immunogold biochip to quantify single extracellular vesicular RNA and protein ( Au SERP) as a non‐invasive alternative. With only 20 μl of purified serum, PD‐1/PD‐L1 proteins on the surface of extracellular vesicles (EVs) and EV PD‐1/PD‐L1 messenger RNA (mRNA) cargo were detected at a single‐vesicle resolution and exceeded the sensitivities of their bulk‐analysis conventional counterparts, ELISA and qRT‐PCR, by 1000 times. By testing a cohort of 27 non‐responding and 27 responding NSCLC patients, Au SERP indicated that the single‐EV mRNA biomarkers surpass the single‐EV protein biomarkers in predicting patient responses to immunotherapy. Dual single‐EV PD‐1/PD‐L1 mRNA detection differentiated responders from non‐responders with an accuracy of 72.2% and achieved an NSCLC diagnosis accuracy of 93.2%, suggesting the potential for Au SERP to provide enhanced immunotherapy predictions and cancer diagnoses within the clinical setting.